Marital Discord Recapturing Human Dignity Through the Higher Objectives of Islamic Law - Abusulayman, Abdulhamid A. (International Institute of Islamic Thought, 2008)
The Quran speaks of living with each other on a footing of love, kindness, mercy and mutual consultation between husband and wife. It also addresses those times when the atmosphere is strained. This paper examines the issue of marital discord with a deep sensitivity to the perspective of women. Criticizing an approach to the Quran that is misogynistic rather than emancipatory the paper moves the debate forward by introducing an alternative interpretation of the Quranic text dealing with the issue of marital discord. The explanation is fresh, firmly on the side of women's human rights and recaptures the full Islamic spirit of human dignity.